Sinonasal/nasopharyngeal pleomorphic adenoma and carcinoma ex pleomorphic adenoma: a report of 17 surgical cases combined with a literature review - Li W (Cancer Management and Research, 2019)
Wanpeng Li, Hanyu Lu, Huankang Zhang, Yuting Lai, Jia Zhang, Yang Ni, Dehui WangDepartment of Otolaryngology-Head and Neck Surgery, Affiliated Eye Ear Nose and Throat Hospital, Fudan University, Shanghai 200031, People’s Republic of ChinaObjective: The aim of this study was to review demographic data, location, clinical symptoms, therapeutic methods, pathological features and relapse in sinonasal/nasopharyngeal pleomorphic adenoma (PA) and carcinoma ex pleomorphic adenoma (CXPA).Methods: We conducted a retrospective analysis of 17 patients who were referred to our hospital during a 5-year period from 2013 to 2018.Results: In this series, there were 7 males and 10 females. The tumors originated from the nasal septum in 4 cases, from the lateral wall of the nasal cavity in 2 cases, from the maxillary sinus in 1 case, and from the nasopharynx in 7 cases. The origin sites of 3 cases were not clear. The main symptoms were usually unilateral nasal congestion and epistaxis. All patients underwent endoscopic resection surgery. The postoperative period was uneventful. Ten patients were diagnosed with benign PA, and 7 patients were diagnosed with CXPA, including 5 cases of adenocarcinoma, 1 patient with mucoepidermoid carcinoma, and 1 patient with adenoid cystic carcinoma. After a mean follow-up period of 2.2 years (6 months–5.3 years), the recurrence rate of benign PA was 10% (1/10); the rate of malignant recurrence was 42.8% (3/7).Conclusion: Sinonasal/nasopharyngeal PA and CXPA are rare neoplasms, and the most common primary site of PA and CXPA is the nasopharynx. As any salivary carcinoma type can arise in PA, these PA sites should be thoroughly sampled and closely examined to exclude the possibility of malignant transformation. Furthermore, PA and CXPA should be treated as soon as possible after definitive diagnosis, and endoscopic resection of tumor-negative margins may be helpful in preventing recurrence.Keywords: sinonasal, nasopharyngeal, pleomorphic adenoma, carcinoma ex- pleomorphic adenoma, endoscopic